Peculiarities of joint pastime of parents with their children in the megalopolis - Tatyana V. Drobysheva; Maria Yu. Voytenko (Известия Саратовского университета. Новая серия. Серия Акмеология образования: Психология развития, 2022)
The study appears to be of relevance due to its focus on differences in the interaction of parents and children in families with different role models (patriarchal, matriarchal, and egalitarian). The purpose of the study is to identify differences in the forms of joint pastime of parents with their child in families of different types. Presumably, the forms of joint pastime of parents with their children differ in families of different types, depending on the role model of the family. In particular, in families with the one-parent-dominance model, the joint pastime of parents with their children will be limited to the performance of their functional duties. Egalitarian families differ in this respect preferring varied forms of joint pastime of parents with their children. The study involved parents of preschoolers living in 11 administrative districts of Moscow. All families are full. The sample (N = 247) included male (45%) and female (55%) parents aged 27 to 48. The following methods were applied: a questionnaire to identify the socio-demographic characteristics of parents and families, their attitudes to the division of family responsibilities; the authors’ original questionnaire aimed at identifying the forms of joint pastime of parents with their children that are preferred by the parents; scaling the psychological well-being of parents (satisfaction with the quality of their interaction with children, with living conditions in the city, and with the comfort of the urban environment for children’s life), and their subjective economic status (developed by V. A. Khashchenko). In order to study the peculiarities of the respondents’ perception of the urban environment, the authors used closed types of questions; the manifestation level of urban identity was revealed with the help of M. Lally’s methodology. The results of the study confirm the hypothesis about the differences in the joint pastime of parents with their children in the families of citizens from families of different types. The research results demonstrate that parents from matriarchal-type families are focused on fulfilling their functional responsibilities connected with caring for their child, but they limit the child’s contacts in the social environment of the megalopolis. In patriarchal-type families, parents shift their responsibility for the child’s upbringing to the spouse and relatives. Their joint activity with the child is limited to the performance of their functional responsibilities connected with caring for the child and to participation in the child’s games. Parents from families with partnership relations are distinguished by having different forms of joint pastime both at home and in the megalopolis. They visit the circus, museums, theaters, shopping centers together with the child, thus expanding the experience of the child’s social interaction with other residents of the city and creating conditions for the socio-psychological well-being of children in the megalopolis. The results of the study indicate the necessity to develop a variety of urban programs for joint pastime of parents with their children. Such programs which will be in demand by different categories of families, primarily with the dominant role of the father or the mother.